Fast Decoupled Power Flow for Unbalanced Radial Distribution System - Singh, Kuldeep (My University, 2009)
Now these days load flow is a very important and fundamental tool for the analysis of any power system and is used in the operational as well as planning stages. Certain applications, particularly in distribution automation and optimization of a power system, require repeated load flow solutions. In these applications it is very important to solve the load flow problem as efficiently as possible. Since the invention and widespread use of digital computers and many methods for solving the load flow problem have been developed. Most of the methods have “grown up” around transmission systems and, over the years, variations of the Newton method such as the fast decoupled method, have become the most widely used. The assumptions necessary for the simplifications used in the standard fast decoupled Newton method often are not valid in distribution systems. In particular, R/X ratios can be much higher. However, some work has been done to attempt to overcome these difficulties. Some of the methods based on the general meshed topology of a typical transmission system are also applicable to distribution systems which typically have a radial or tree structure. Specifically, we will compare the proposed method to the standard Newton method, and the implicit Zbus Gauss method. These methods do not explicitly exploit the radial structure of the system and therefore require the solution of a set of equations whose size is of the order of the number of buses. Our goal was to develop a formulation and solution algorithm for solving load flow in large three-phase unbalanced systems which exploits the radial topological structure to reduce the number of equations and unknowns and the numerical structure to further reduce computation as in the fast decoupled methods for distribution systems.
Keywords: Radial distribution system, load flow techniques, fast decoupled load flow method